The Influence of Organizational Support, Team Collaboration, and Job Security on Job Satisfaction of Health Workers at Regional General Hospitals - Tawil, Muhamad Risal; Subroto, Desty Endrawati; Anantadjaya, Samuel PD; Nawangwulan, Irma M; Violin, Vivid; Putranto, Samuel Aditya Eko (Yayasan Gema Bina Nusantara, 2026)
The study examines the effects of organizational support and team collaboration and job security on job satisfaction among healthcare staff working in a regional general hospital. The study used quantitative research methods which involved researchers distributing questionnaires to 130 selected participants who were chosen through purposive sampling. The researchers conducted data analysis by using multiple linear regression which needed testing of both validity and reliability together with normality testing and heteroscedasticity testing and multicollinearity testing. The research found that organizational support and team collaboration and job security positively impacted job satisfaction which reached statistically significant results. Healthcare workers can perform their duties in a secure work environment which exists because organizations provide support and teams work together and employees have job security. The three variables together explain all changes that occur in job satisfaction levels. The study results assist hospital administrators in developing successful plans which will enhance healthcare worker job satisfaction and improve healthcare service delivery.